Football Fans' Views on the Passolig E-Ticket System and the Decrease in Stadium Attendance: The Case of the Turkish Football Super League - Çakmak Gökhan; Çiftçi Sevda (Sciendo, 2021)
The aim of this research is to investigate the reasons behind the decline in stadium attendance in the Turkish Football Super League since the implementation of the Passolig e-ticket system as well as football fans' views on this system. The research sample consisted of football fans living in the province of Sakarya. The total number of participants was 500. A questionnaire comprising three parts was used for data collection. The first part of the questionnaire included questions aimed at identifying personal details of the participants; the second part included questions intended to identify their viewpoints on Passolig; the third part asked about their opinions concerning the reasons behind the decline in stadium attendance. The questionnaire contained 38 questions in total, 37 of which were prepared in the form of a five-point Likert scale with an additional open-ended question to identify participants' opinions of Passolig. Quantitative data obtained through the study were evaluated using the IBM SPSS 25.0 software package, and qualitative analysis methods were employed for coding the questions about participants' opinions. The study concluded that based on the opinions of the participants, Passolig has not been able to fulfill its intended functions of increasing stadium attendance, minimizing violence, and preventing ticket touting. The participants view Passolig as a means of generating unearned income and understand its implementation as one of the main reasons for the decline in stadium attendance. Besides the implementation of Passolig, high ticket prices, the weak financial situation of fans, and media broadcasts that provoke violence were among the foremost reported reasons for the decline in stadium attendance.